THE COMPOSITION OPERA TOR Cp ON HARDY SPACE H2 - Abood, Eiman (Iraqi Journal of Science, 2024)
In this paper, we characterize the unitary composition operator pC on the Hardy space 2H where p is a special automorphism of a unit open disk U such that. In addition to we study the compactness and essential normality of and give some other partial results.